Chronic flavanol-rich cocoa powder supplementation reduces body fat mass in endurance athletes by modifying the follistatin/ myostatin ratio and leptin levels. - Moreno Pérez, Diego; García Merino, Jose Angel; Montalvo-Lominchar, María Gregoría; Sánchez, Lara; de Lucas, Beatriz; Muñoz, Elsa; naclerio, fernando; Herrera-Rocha, Karen Marlene; Larrosa, Mar (My University)
El cacao es uno de los alimentos que tiene mayor contenido de flavonoles. En los últimos años, ha crecido el interés por sus posibles beneficios. A nivel de salud, se ha demostrado que la ingesta de cacao, provoca cambios positivos en la composición corporal. En cambio, en rendimiento deportivo, apenas existen referencias que nos indiquen sus posibles ventajas. Esta es la razón por la que se decidió llevar a cabo esta investigación, con el fin de evaluar los efectos de la suplementación con cacao en corredores entrenados durante un programa regular de carrera a pie de 10 semanas en (a) rendimiento deportivo y (b) composición corporal. La ingesta diaria de 5gr de cacao disminyó significativamente el porcentaje de masa grasa (p = 0.020), a nivel de tronco (p = 0.022), área visceral (p = 0.034) y piernas (p = 0.04). La reducción en la masa grasa fue acompañado de un incremento en plasma de la folistatina y un descenso en la leptina. No existieron cambios en el rendimiento deportivo.

Flavanols-rich cocoa has positive effects on lipid metabolism and might enhance the performance of athletes through an improvement in their body composition. To test this hypothesis a placebo-controlled intervention study in training endurance athletes who received 5 g of cocoa daily (425 mg of flavanols) for 10 weeks was performed. Dietary intake, body composition, exercise performance and plasma levels of follistatin, myostatin and leptin were measured. Cocoa intake significantly reduced body fat percentage (p = 0.020), specifically in the trunk (p = 0.022), visceral area (p = 0.034) and lower limbs (p = 0.004). The reduction in body fat mass was accompanied by an increase in plasma follistatin and a decrease in leptin, while myostatin levels remained unchanged. The intake of cocoa reduced the percentage of body fat of athletes, without any impact on athletes' performance. The change in fat body composition did not improve athletes' performance
Artículos en revistas